Russia's unfinished revolution : political change from Gorbachev to Putin - McFaul, Michael, 1963- (Ithaca, N.Y. : Cornell University Press, 2001)
For centuries, dictators ruled Russia. Tsars and Communist Party chiefs were in charge for so long some analysts claimed Russians had a cultural predisposition for authoritarian leaders. Yet, as a result of reforms initiated by Mikhail Gorbachev, new political institutions have emerged that now require election of political leaders and rule by constitutional procedures. Michael McFaul traces Russia's tumultuous political history from Gorbachev's rise to power in 1985 through the 1999 resignation of Boris Yeltsin in favor of Vladimir Putin. McFaul divides his account of the post-Soviet country into three periods: the Gorbachev era (1985-1991), the First Russian Republic (1991-1993), and the Second Russian Republic (1993-present). The first two were, he believes, failures -- failed institutional emergence or failed transitions to democracy. By contrast, new democratic institutions did emerge in the third era, though not the institutions of a liberal democracy. McFaul contends that any explanation for Russia's successes in shifting to democracy must also account for its failures. The Russian/Soviet case, he says, reveals the importance of forging social pacts; the efforts of Russian elites to form alliances failed, leading to two violent confrontations and a protracted transition from communism to democracy. -- Description from http://carnegieendowment.org (April 19, 2012).
The Revolutionary Transition from Communism to Democracy: A Model --- The Gorbachev Era, 1985-1991 --- Gorbachev's Design for Reforming Soviet Political Institutions --- The End of the Soviet Union --- The First Russian Republic, 1991-1993 --- Institutional Design in the First Russian Republic --- The Failure of the First Russian Republic --- The Emergence of the Second Russian Republic, 1993-1996 --- Designing the Political Institutions of the Second Republic --- Transitional Constitutionalism --- Transitional Electoralism --- The Future of Russian Democracy --- The Quality of Russian Democracy --- The Stability of Partial Democracy.
Includes bibliographical references and index.
E-Book-ACLS / Zugriff nur im DHI-Lesesaal
American Council of Learned Societies/ https://www.humanitiesebook.org/about
Keywords: Gorbachev, Mikhail Sergeevich, -- 1931-2022.; Putin, Vladimir Vladimirovich, -- 1952-; Russia (Federation) -- Politics and government -- 1991-; Soviet Union -- Politics and government -- 1985-1991.; Soviet Union -- Politics and government -- 1991-; Soviet Union -- Economic policy -- 1985-1991.; Soviet Union -- Economic policy -- 1991-; Russia (Federation); Soviet Union; Electronic books; Democracy; Democracy